Teknik Reframing Dalam Membantu Permasalahan Komunikasi Keluarga Pada Anak Binaan - Hilyah Auliah Al-Azim; Micha Felayati Silalahi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aimed to examine the application of reframing techniques in addressing family communication problems among juvenile inmates at the Class II Special Development Institution for Children (LPKA) in Palu. Family communication problems may affect the psychological well-being of juvenile inmates and their social reintegration process. Therefore, counseling interventions through reframing techniques are considered a potential strategy to support the improvement of family communication. This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The population consisted of 24 juvenile inmates, and the total sampling technique was applied. Data were collected using questionnaires and analyzed through simple linear regression and t-test with the assistance of SPSS. The results indicated an increase in family communication scores following the implementation of reframing techniques. Statistical analysis showed a regression coefficient of 0.608 with a significance value of 0.000 (< 0.05), suggesting a positive association between the implementation of reframing techniques and improvements in family communication among the participants. These findings indicate that reframing techniques have the potential to support the improvement of family communication among juvenile inmates and may be considered as an alternative strategy in guidance and counseling services at LPKA. However, due to the absence of a control group, the findings should be interpreted with caution and do not fully establish a causal relationship.